PARENTING PATTERNS AND PREVENTION OF DISCRIMINATORY BEHAVIOR IN YOUNG CHILDERN IN PATI - Aulia, Zahro; Purnama, Sigit; Sibawaihi; 'Aziz, Hafidh; Adikusuma, Melati Puspitajati (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2025)
Childhood is a fundamental stage in the formation of individual character and social behavior, particularly regarding acceptance or rejection of diversity. Children aged 4–6 years are in a highly sensitive developmental phase where parenting styles play a central role in shaping how they perceive differences. This study aims to analyze the influence of parenting styles on the tendency toward discriminatory behavior in early childhood in Kertomulyo Village, Pati Regency. Using a qualitative approach and case study method involving four families, data were collected through online interviews and analyzed using Miles and Huberman’s interactive model. The findings reveal that modern parenting styles such as positive parenting, mindful parenting, and gentle parenting when applied consistently, can foster empathy, tolerance, and acceptance of differences. Conversely, inconsistent parenting, authoritarian styles, excessive protectiveness, or lack of supervision over digital media consumption can contribute to the development of discriminatory attitudes in children. These findings underscore the crucial role of parents in instilling inclusive values and shaping children's character from an early age, as well as the need for collaboration among families, educational institutions, and communities in creating environments that support the growth of a tolerant and just generation